Porous SNO2/TI dimensionally stable anode for degradation of pollutants from water synthesis and morphostructural characterization - Orha Corina (Proceedings of the International Symposium on Analytical and Environmental Problems, 2020)
In this work, the protocol based on Doctor-Blade method for synthesis of porous SnO2/Ti dimensionally stable anode suitable for advanced treatment of water/wastewater is presented. Prior to SnO2/Ti synthesis, SnO2 was obtained by sol-gel method using SnCl2 as Sn precusor and polyethylene glycol. The morpho-structural characterization through X-ray diffraction (XRD) and scanning electron microscopy coupled with energy-dispesive X-ray (SEM/EDX) confirmed an uniform deposition of SnO2 mesoporous on the Ti surface with typical mud cracked-like structure, which should be suitable for the further water treatment application.